Forecasting the Impact of Climatic Factors on Sand Dune Mobility in the Salt Lake Basin using Sensitivity Analysis. - Leila Biabani; Hassan Khosravi; Gholamreza Zehtabian; Esmaeil Haydari Alamdarloo; Behzad Rayegani (Desert)
Due to its location in in the arid and semi-arid region of central Iran, The Salt Lake basin is constantly affected by erosive winds leading to the transportation and deposition of sediments. The annual transfer of fine sand causes significant damage to residential areas, transportation routes, and agricultural land. Over a 20-year period, the level of sand dune activity was investigated in the Salt Lake basin using the data of 15 synoptic stations. The climatic factors including hourly wind speed, dust storm phenomenon codes, rainfall, temperature, evaporation, and transpiration were analyzed to determine the Lancaster index. The results of this index indicated that sand dune activity is dormant sand dunes in 67% of stations, 27% active only in sand dune canopy areas, and 7% active. The stabilization of sand dunes resulted from management measures such as arboriculture, afforestation, grazing management, rangeland exclusion, and mulch. Also, the highest and lowest frequency of days with dust is Arak station with 5460 days and Abali station with 148 days respectively. Based on the aridity index, the region is considered semi-arid to arid. It is at high risk for desertification. According to the sensitivity analysis test, it was determined that a 30% increase in erosive winds would result in a corresponding 30% increase in sand dune activity and movement. Conversely, a 30% rise in rainfall would lead to a 43% decline in sand dune activity. Finally, the mobility of sand dunes is more sensitive to changes in rainfall than wind speed.